Systemic osteoprotective effects of Epimedii Folium and Ligustri Lucidi Fructus in senile osteoporosis rats by promoting the osteoblastogenesis and osteoclastogenesis based on MLP-ANN model - Xiu-Feng Tang; Zi-Tong Ma; Ying-Ying Gao; Han Wang; Xiao-Xi Li; Ping Yu; Ren-Hui Liu (BMC, 2020)
Abstract Background Senile osteoporosis (SOP), which is caused by unbalanced bone remodeling, leads to significant economic and societal burdens globally. The combination of Epimedii Folium (EF) and Ligustri Lucidi Fructus (LLF) serves as a commonly-used prescription for SOP in Traditional Chinese Medicine (TCM). This study aimed to evaluate the osteoprotective effects of EF and LLF in combination on SOP rats based on the constructed multilayer perception (MLP)-artificial neural network (ANN) model. Methods 15 month old male Sprague-Dawley rats were administrated with EF, LLF or the combination of EF and LLF (EF&LLF) for 2 months, while 17 month old rats were used as the aging control group. All the rats were anesthetized with 25% ethyl carbamate, then their serum liver and bone tissues were taken. We detected bone mass, bone mineral density (BMD), biomechanics and the microstructure of bone trabecula by micro-CT and H&E staining to evaluate the degree of osteoporosis. Blood lipids and serum alanine aminotransferase (ALT), aspartate aminotransferase (AST) and γ-glutamyl transferase (GGT) and liver pathology were use to assess the side effects of drugs. Levels of alkaline phosphatase (ALP) and Tartrate-resistant acid phosphatase (TRACP) and the ratio of ALP to TRACP both in serum and bone were measured for the evaluation of bone turnover rate. The bone mRNA and protein expression of osteoprotegerin (OPG), nuclear factor-kappa B ligand (RANKL), macrophage colony-stimulating factor (M-CSF), d2 isoform of vacuolar (H+) ATPase (ATP6V0d2), insulin-like growth factor (IGF-1), bone morphogenetic protein-2 (BMP2), M-CSF, Wnt5a, transforming growth factor-β1 (TGF-β1) were detected for evaluating bone metabolism. Results The results showed that EF&LLF improved bone mass and bone quality by preventing bone loss, increasing maximal load as well as protecting the micro-structural retrogressive change of trabecular bone in SOP rats; ameliorated the steatosis in the liver and decreased blood lipids and serum ALT, AST and GGT; enhanced bone remodeling by stimulating the expression of ALP and TRACP. At the molecular levels, EF&LLF stimulated the osteoclastogenesis by upregulating the protein and mRNA expression of OPG, RANKL, M-CSF and ATP6V0d2; meanwhile, EF&LLF stimulated osteoblastogenesis by enhancing the expression of TGF-β1, BMP2, Wnt5a and IGF-1. According to our established MLP model, EF&LLF has a better effect on osteoclastogenesis or steoblastogenesis in SOP rats than EF or LLF. Conclusions These findings demonstrate that the systemic bone protective effects of EF&LLF by promoting bone remodeling in aging rats might be a substitute medicine for the treatment of SOP.